SUSCEPTIBILITY MAGNETIC AND HIGH MAGNETIC FIELD ESR MEASUREMENT OF SrCu2 (PO4 )2 - Aripin, Aripin; Mitsudo, Mitsudo; Idehara, T.; Mekata, M (UI Scholars Hub, 2007)
The magnetic susceptibility and high magnetic ESR measurement of SrCu2 (PO4 )2 has been performed at temperatures ranging from 4.2 K to 300 K and 4.2 K to 77 K, respectively. The magnetic susceptibility shows a broad maximum around T = 40 K. The magnetic susceptibility has been interpreted in terms of one-dimensional magnetic systems. The temperature dependence of the magnetic susceptibility indicated a good agreement with 4-spin alternating configuration model. In the ESR measurement, clear electron spin resonance (ESR) was observed. The integrated intensity for 120 and 301 GHz has a broad maximum at around 40 K, which is consistent with the susceptibility result. A quantitative description gives resonance is the first and second triplet excited states of the excitation spectrum of 4-spin alternating chain configuration. The g1 , g2 and g3 values are approximately 2.21 at temperature above 40 K. The g2 dan g3 values have the dependence of temperature under 40 K.